CYSTIC ECHINOCOCCOSIS IN THE FAR EASTERN FEDERAL DISTRICT: CURRENT STATE OF THE PROBLEM - A. G. Dragomeretskaya; O. E. Trotsenko; L. A. Bebenina; O. P. Kurganova; M. E. Ignateva; T. A. Zaitseva; P. V. Kopylov; D. V. Maslov; N. I. Zhdanova; A. A. Rubtsova; O. A. Funtusova; I. Yu. Fedelesh (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Aim. To analyze current epidemiological and epizootological situation on cystic (hydatidiform) echinococcosis in constituent entities of the Far Eastern Federal District (FEFD) of the Russian Federation. Materials and methods. Data of the administrations of the Federal service for surveillance on consumers rights protection and human wellbeing as well as data of the FBIH «Center of hygiene and epidemiology» located in different constituent territories of the FEFD during 2013-2017 was used. A review of scientific papers concerning the topic of the current article was performed. Results. Mainly sporadic cases of the disease were registered in 7 out of 9 constituent entities of the FEFD during the 2013-2017. The Jewish Autonomous district and Kamchatka region were free of the echinococcosis during the 5-year observation period. Echinococcosis cases were registered annually in the Chukotka Autonomous district, Republic Sakha (Yakutia) and Primorsky region. Herewith, the incidence rates in Chukotka Autonomous district and Republic Sakha (Yakutia) notably exceeded the national average. No fatal outcomes due to cystic echinococcosis in the FEFD were registered. Conclusion. Implementation of immunoepidemiological surveillance of the population of different age groups and professions is recommended on the constituent entities with registered cases of cystic echinococcosis.